A Preliminary Study for Distinguish Hormone-Secreting Functional Adrenocortical Adenoma Subtypes Using Multiparametric CT Radiomics-Based Machine Learning Model and Nomogram - Zheng, Yineng; Liu, Xin; Zhong, Yi; Lv, Fajin; Yang, Haitao (Frontiers in Oncology, 2020)
Purpose: To explore the application value of multi-parametric computed tomography (CT) radiomics in non-invasively differentiating aldosterone-producing and cortisol-producing functional adrenocortical adenomas. Methods: This retrospective review analyzed 83 patients including 41 patients with aldosterone-producing adenoma and 42 patients with cortisol-producing adenoma. A total of 627 quantitative radiomics features were extracted from the complete unenhanced, arterial and venous phase CT images. A comparative study of several frequently-used machine learning models (linear discriminant analysis, logistic regression, random forest and support vector machine) combined with different feature selection methods was implemented in order to determine which was most advantageous for differential diagnosis using radiomics features. Then, the integrated model using the combination of radiomic signature and clinic-radiological features was built, and the associated calibration curve was also presented. The diagnostic performance of these models was estimated and compared using the area under the receiver operating characteristic (ROC) curve (AUC). Result: In the radiomics based machine learning model, logistic regression model with LASSO outperformed the other models, which yielded a sensitivity of 0.935, a specificity of 0.823 and an accuracy of 0.887 (AUC = 0.882, 95% CI: 0.819, 0.945). Moreover, the nomogram representing the integrated model achieved good discrimination performances which yielded a sensitivity of 0.915, a specificity of 0.928 and an accuracy of 0.922 (AUC = 0.902, 95% CI: 0.822, 0.982), and it was better than that of the radiomics model alone. Conclusion: This study found that using the combination of multi-parametric radiomics signature and clinic-radiological features can non-invasively differentiate the subtypes of hormone-secreting functional adrenocortical adenomas, which may have good potential for facilitating the diagnosis and treatment in clinical practice.